Variation in Weight of Milled Raw Rice During Storage - Kudos, SK Aleksha; Oberoi, Harinder Singh; Baboo, Bangali; Chadda, I C (Journal of Agricultural Engineering, 2006)
A study on storage of rice was conducted to find the effect of moisture content on the weight of milled raw rice for a period of one-year under stacking condition and the correlation between loss or gain in weight of rice on moisture content basis and actual weighment basis was determined. During the period from March to May and September to November there were continuous losses in the weight of rice whereas in the months of January- February and the period from June to August there was continuous gain in weight. The results indicated a positive correlation (0.88) between the losses based on moisture content and actual weighment. It was also found that 89% of the total variation in the loss or gain in the weight of rice (PR-114) could be accounted for by a linear function involving the monthly mean relative humidity of the store room in addition to the difference in moisture content.